2011
DOI: 10.1002/cbdv.201100081
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Sugar‐Modified Oligonucleotides for Antisense Therapeutics

Abstract: Among the multitude of chemical modifications that have been described over the past two decades, oligonucleotide analogs that are modified at the 2'-position of the furanose sugar have been especially useful for improving the drug-like properties of antisense oligonucleotides (ASOs). These modifications bias the sugar pucker towards the 3'-endo-conformation and improve ASO affinity for its biological target (i.e., mRNA). In addition, antisense drugs incorporating 2'-modified nucleotides exhibit enhanced metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
96
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(97 citation statements)
references
References 104 publications
0
96
0
1
Order By: Relevance
“…42 We therefore anticipate that C5 functionalization of pyrimidines will serve as a general and synthetically straightforward approach for modulation of pharmocodynamic and pharmacokinetic properties of oligonucleotides modified with LNA 810,13 or other conformationally restricted monomers. 17,16 Efforts aiming at delineating whether the biophysical properties of LNA purines also can be improved through functionalization of the nucleobase are ongoing, and the results from these studies will be reported shortly.…”
Section: Resultsmentioning
confidence: 99%
“…42 We therefore anticipate that C5 functionalization of pyrimidines will serve as a general and synthetically straightforward approach for modulation of pharmocodynamic and pharmacokinetic properties of oligonucleotides modified with LNA 810,13 or other conformationally restricted monomers. 17,16 Efforts aiming at delineating whether the biophysical properties of LNA purines also can be improved through functionalization of the nucleobase are ongoing, and the results from these studies will be reported shortly.…”
Section: Resultsmentioning
confidence: 99%
“…These challenges can be minimized by chemical modifications of ODNs to enhance their pharmacokinetic and pharmacodynamic properties [4,6]. These chemical modifications include: sulfurization of the phosphodiester bond to avert degradation by enlindogenous exonucleases, addition of methoxy or methoxyethyl groups to sugar moieties [7,8], locked and unlocked nucleic acids, and alterations in the internucleotide linkage (e.g., amide linkage) resulting in peptide nucleic acids [1]. Sulfurization results in phosphorothioate analogs that are more hydrophobic, exhibit more complex secondary structures with higher protein binding and greater accumulation in organs than phosphodiester analogs [9][10][11].…”
mentioning
confidence: 99%
“…13.5). Nucleic acid analogs that have these properties are 2′-O-alkyl derivatives, thiophosphates, morpholidates (mORF), locked nucleic acids (LNAs), and PNAs [73][74][75][76]. Some of these analogs also show enhanced binding affinity for RNA, such as the LNAs and PNAs.…”
Section: Stable Antisense Odn Analogs For Imagingmentioning
confidence: 99%